Hubungan Literasi Kesehatan Reproduksi dengan Perilaku Seksual pada Remaja Pertengahan - Delli Yuliana Rahmat; Dewi Dolifah; Diding Kelana Setiadi (Universitas Nurul Jadid, 2026)
Reproductive health literacy is an individual's ability to access, understand, assess, and apply information regarding reproductive functions and processes, which is expected to influence adolescent sexual behavior. This study aimed to determine the relationship between reproductive health literacy and the sexual behavior of middle adolescents. A quantitative research design with a correlational approach was employed, involving 137 respondents selected through accidental sampling. Data were collected using validated and reliable Likert-scale questionnaires for reproductive health literacy and sexual behavior. Data analysis was performed using the Fisher’s Exact Test. The results indicated that the majority of respondents possessed good reproductive health literacy (85.4%), while only a small percentage reported engaging in sexual behavior (1.5%). Statistical analysis yielded a p-value of 0.272 (p > 0.05). In conclusion, there is no significant relationship between reproductive health literacy and the sexual behavior of middle adolescents at SMA N 1 Cimalaka. Efforts to prevent risky sexual behavior include strengthening family roles, providing counseling, fostering positive social environments, monitoring media use, and encouraging participation in organized activities, sports, arts, and religious programs. Limitations of this study include a design that cannot establish causality and an imbalanced data distribution that may influence the analysis.